An in vitro study for the evaluation of morphological and biochemical characteristics of absorbable sutures coated with genistein and nicotine - Chopra, Aditi; Cecil, Anju; Eshwaramoorthy, Rajalaksmanan; John, Rubin S. (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Inflammation, cell proliferation, matrix deposition, and tissue remodeling are all elements of the well-structured and well-coordinated process of wound repair. The aim of this study was to analyze the effect of genistein and nicotine on polyglycolic acid (PGA) and vicryl sutures. Material and methods. Genistein and nicotine were isolated and solution was prepared and the suture material PGA and vicryl were immersed in the solution and dried. They were tested for their tensile strength and degradation values after immersion in artificial saliva (on the first day and on the 14th day). The sutures were also seen under a scanning electron microscope (SEM) for its uniform coating and the mixture formulation of genistein and nicotine were tested for their anti-inflammatory and antioxidant activity using protein denaturation assay and 2,2-diphenyl-1-picrylhydrazyl assay respectively. Results. Nicotine has a high anti-inflammatory activity on the suture material, whereas Genistein has an insignificant anti-inflammatory effect. The mixture formulation has a relatively similar anti-inflammatory effect when compared to the control. The SEM analysis shows a uniform coating of the formulation on the PGA and vicryl sutures. In comparison, PGA has shown lesser tensile strength and hence higher degradation ability. Conclusion. Nicotine and Genistein affect the tensile strength and degradation properties of the sutures.
Keywords: absorbable sutures; antiinflammatory; antioxidant; genistein; nicotine; tensile strength